TRANSFORMASI AUDIT INTERNAL MODERN: MENINGKATKAN EFEKTIVITAS MANAJEMEN ORGANISASI - Dwiyanto, Muhaswad; Supriadi, Yudi Nur (Gapenas Publisher, 2024)
Supervision, both internal and external, plays a crucial role in organizational control in both public and private sectors. In the public sector, the Government Internal Supervisory Apparatus (APIP) includes Inspectorates of Ministries/Agencies, the Financial and Development Supervisory Agency (BPKP), and Inspectorates of Provinces/Districts/Cities, while external supervision is carried out by the Supreme Audit Agency of the Republic of Indonesia (BPK-RI). Over time, the concept of internal supervision has undergone significant transformation. The definition of internal audit now encompasses both assurance and consulting activities, aimed at adding value to the auditee organization. Internal auditors now act not only as error watchdogs but also as partners providing solutions to organizational issues. Achieving effective internal supervision and delivering tangible benefits requires internal auditors to provide value-added recommendations and integrate risk management as a key component. Additionally, fostering integrity between auditors and auditees is essential to dispel the negative stigma that internal auditors only bring bad news. Therefore, understanding the modern concept of the internal auditor's role is crucial for leaders, internal auditors, and all auditees. Effective implementation of risk management by auditees will assist internal auditors in establishing effective controls and operational oversight, thereby fostering a healthier and more efficient organizational environment